Evaluation of the Efficacy and Safety of PARP Inhibitors in Advanced-Stage Epithelial Ovarian Cancer - Jiang, Yifan; Zhao, Juan; Zhang, Li; Tian, Sijuan; Yang, Ting; Wang, Li; Zhao, Minyi; Yang, Qing; Wang, Yaohui; Yang, Xiaofeng (Frontiers in Oncology, 2020)
Purpose: PARP inhibitors are a novel targeted anti-cancer drugs and a large number of clinical studies on PARP inhibitors have been accomplished. This updated meta-analysis was conducted to evaluate the efficacy and safety of PARP inhibitors in the maintenance treatment of advanced stage epithelial ovarian cancer. Methods: Medline (PubMed), Embase, Cochrane Central Register of Controlled Trials, Web of Science, and Scopus were searched to identify the eligible trials up to January 2020. CinicaTrias.gov. was also screened for additional unpublished trials. Data extraction and risk of bias assessment were performed by two independent investigators respectively. The hazard ratios (HRs) and its 95% confidence intervals (CI) for time-to-event data of progression-free survival (PFS) and overall survival (OS), and the risk ratios (RRs) with 95% CI for dichotomous data of overall response rate (ORR) and occurrence of AEs were calculated by Review Manager 5.3 and Stata 12.0 software. Results: A total of 11 trials with 4158 patients were included in this meta-analysis. Compared with the control group, PARP inhibitors significantly improved PFS (HR, 0.46; 95% CI, 0.37-0.57; P < 0.00001) and ORR (RR, 1.31; 95% CI, 1.15-1.49; P < 0.0001). Specifically, PFS was improved regardless of BRCA genes mutations and homologous-recombination status. However, no difference was observed in OS between the PARP inhibitors group and the control group (95% CI, 0.73-1.01; P = 0.06). PARP inhibitors was associated with a statistically significant higher risk of hematologic events and different PARP inhibitors had different toxicities profile. Conclusion: PARP inhibitors is an effective and well-tolerated maintenance treatment for patients with advanced stage epithelial ovarian cancer.